Can "domino" therapy effectively treat the infection around the prosthesis after the limb salvage surgery of bone tumor? - A study of sequential therapy. (May 2022) - Mou, Haochen; Qu, Hao; Li, Binghao; Wang, Shengdong; Li, Hengyuan; Li, Xiumao; Zhang, Wenkan; Teng, Wangsiyuan; Zhang, Zengjie; Wang, Keyi; Wang, Fangqian; Sun, Hangxiang; et al.
Abstract: Background: Tumor resection and prosthetic replacement have become the treatments of choice for malignant bone tumors. Infections are the leading cause of failure of limb salvage surgeries. Therefore, treating infections around prostheses after limb salvage is essential and challenging. Our research team designed a "domino" sequential treatment plan to treat postoperative infections around tumor prostheses and evaluated its efficacy. Purpose: To introduce the new domino sequential treatment plan for postoperative infections of tumor prostheses, and evaluate the technical points of the plan and prognosis in medium- and long-term follow-ups. Methods: Between January 2015 and August 2021, 14 patients were treated with prosthesis-preserving domino sequential therapy for peripheral prosthesis infections after bone-tumor limb salvage. The sample included eight cases of distal femur tumor, two of proximal tibia tumor, three of pelvic tumor, and one of middle femur tumor. We evaluated routine blood test results, C-reactive protein level, the erythrocyte sedimentation rate, and other indicators. X-rays and CT scans of the surgical site were obtained and the Musculoskeletal Tumor Society (MSTS) score was calculated. Treatment involved debridement and lavage of the prosthesis, and systemic and local antibiotics. Results: The positivity rate of microbial culture was 78.6%. There were three cases of Staphylococcus aureus, one of Staphylococcus epidermidis, two of methicillin-resistant Staphylococcus epidermidis, one of methicillin-resistant Staphylococcus aureus, two of Acinetobacter baumannii, one of Streptococcus lactis (group C), one of Streptococcus mitis, and three with negative cultures. In three cases, sequential treatment failed to control the infection. The operation success rate was 78.6% (11/14). One case eventually required amputation, and another required long-term wound dressings. To control the infection, a third had to be treated using antibiotic bone cement combined with the "intramedullary nail reverse double insertion" technique. The MSTS scores of patients before infection debridement and at the last follow-up showed statistically significant differences (t = 5.312, p = 0.02). Conclusions: The prosthesis-preserving domino sequential method has certain advantages for treating bone-tumor limb salvage infections around the prosthesis. Level of evidence: Level IV, therapeutic. Highlights: We evaluated the therapy effect of the sequential therapy. Introduce a new type of domino sequential treatment plan for treating postoperative infections of tumor prosthesis. We evaluate the technical points of the plan, and prognosis over medium- and long-term follow-ups.